A Review of Thin-Film Magnetoelastic Materials for Magnetoelectric Applications - Xianfeng Liang; Cunzheng Dong; Huaihao Chen; Jiawei Wang; Yuyi Wei; Mohsen Zaeimbashi; Yifan He; Alexei Matyushov; Changxing Sun; Nianxiang Sun (Sensors, 2020)
Since the revival of multiferroic laminates with giant magnetoelectric (ME) coefficients, a variety of multifunctional ME devices, such as sensor, inductor, filter, antenna etc. have been developed. Magnetoelastic materials, which couple the magnetization and strain together, have recently attracted ever-increasing attention due to their key roles in ME applications. This review starts with a brief introduction to the early research efforts in the field of multiferroic materials and moves to the recent work on magnetoelectric coupling and their applications based on both bulk and thin-film materials. This is followed by sections summarizing historical works and solving the challenges specific to the fabrication and characterization of magnetoelastic materials with large magnetostriction constants. After presenting the magnetostrictive thin films and their static and dynamic properties, we review micro-electromechanical systems (MEMS) and bulk devices utilizing ME effect. Finally, some open questions and future application directions where the community could head for magnetoelastic materials will be discussed.